Histamine H2 receptor signaling × environment interactions determine susceptibility to experimental allergic encephalomyelitis. Issue 4 (26th December 2013) - Saligrama, Naresha; Case, Laure K.; Krementsov, Dimitry N.; Teuscher, Cory
Abstract : Histamine and its receptors are important in both multiple sclerosis and experimental allergic encephalomyelitis (EAE). C57BL/6J (B6) mice deficient for the histamine H2 receptor (H2 RKO) are less susceptible to EAE and exhibit blunted Th1 responses. However, whether decreased antigen‐specific T‐cell effector responses in H2 RKO mice were due to a lack of H2 R signaling in CD4 + T cells or antigen‐presenting cells has remained unclear. We generated transgenic mice expressing H2 R specifically in T cells on the H2 RKO background, and, using wild‐type B6 and H2 RKO mice as controls, induced EAE either in the presence or absence of the ancillary adjuvant pertussis toxin (PTX), which models the effects of infectious inflammatory stimuli on autoimmune disease. We monitored the mice for clinical signs of EAE and neuropathology, as well as effector T‐cell responses using flow cytometry. EAE severity and neuropathology in H2 RKO mice expressing H2 R exclusively in T cells become equal to those in wild‐type B6 mice only when PTX is used to elicit disease. EAE complementation was associated with frequencies of CD4 + IFN‐γ + and CD4 + IL‐17 + cells that are equal to or greater than those in wild‐type B6, respectively. Thus, the regulation of enceph‐alitogenic T‐cell responses and EAE susceptibility by H2 R signaling in CD4 + T cells is dependent on gene × environment interactions.—Saligrama, N., Case, L. K., Krementsov, D. N., Teuscher, C. Histamine H2 receptor signaling × environment interactions determine susceptibility to experimental allergic encephalomyelitis. FASEB J. 28, 1898–1909 (2014). www.fasebj.org